Visas of life and the epic journey how the Sugihara survivors reached Japan - Kitade, Akira 1944- (Tōkyō Chōbunsha, 2014)
"The untold stories of Japanese civilians who transported Jewish refugees to safety in WWII"--Cover overlay.
Prologue : one phone call -- The untold stories of JTB's [Japan Tourist Bureau's] contribution -- The pictures in the album -- Port of humanity, Tsuruga -- Visiting the "Sugihara children" -- Traces of Jewish refugees : Kobe in 1941 -- The role of Nippon Yusen Kaisha (NYK) -- Lyric for Hikawa-maru.
Colophon chiefly in Japanese.
Keywords: Sugihara, Chiune -- 1900-1986.; Japan Tsūrisuto Byūrō.; Nihon Yūsen Kabushiki Kaisha; World War, 1939-1945 -- Jews -- Rescue -- Japan; World War, 1939-1945 -- Jews -- Rescue -- Lithuania; Righteous Gentiles in the Holocaust -- Japan